2009
DOI: 10.1002/poc.1559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high fluorescent silica hybrid materials by immobilization of orange peel extract in silica‐silsesquioxane matrix

Abstract: Sol–gel chemistry can be easily modified to the changing needs of society to produce fine‐tuned sol–gel nanostructured materials for relevant applications. In this context, there is an increasing need for natural and versatile raw materials as well as biocompatible compounds that could be extensively used as biomarkers for bioimaging in diagnosis or therapy. Silica‐based materials are widely used in the field of biomedicine due to their chemical inertness and biocompatibility. In the present paper, orange peel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…After the first two experiments the film with 4:1 ratio has been no longer characterized and discussed, due to the decreasing degree of the optical transparency, visible by free eye and confirmed, as can be seen later, from fluorescence measurements of the film prepared with a higher amount of OMEOS. Regarding the composition of organic fluorescent components, from our previous studies [16,17] it was demonstrated that 2% organic component embedded into a hybrid silica-silsesquioxane network was optimum for a good compatibility that assures an appropriate confinement inside internal network and avoids the aggregation of vegetal mixtures that leads to the quenching of fluorescence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…After the first two experiments the film with 4:1 ratio has been no longer characterized and discussed, due to the decreasing degree of the optical transparency, visible by free eye and confirmed, as can be seen later, from fluorescence measurements of the film prepared with a higher amount of OMEOS. Regarding the composition of organic fluorescent components, from our previous studies [16,17] it was demonstrated that 2% organic component embedded into a hybrid silica-silsesquioxane network was optimum for a good compatibility that assures an appropriate confinement inside internal network and avoids the aggregation of vegetal mixtures that leads to the quenching of fluorescence.…”
Section: Discussionmentioning
confidence: 98%
“…As a result it became increasingly attractive to use the film in a variety of applications such as microelectronics [12], catalysis [13], biotechnology [14] etc. The possibility of introduction of optically active/photoactive molecules without their degradation, physically or covalently bounded in a hybrid sol-gel network has been increased over the last few years [15][16][17], since they excite much interest in the fluorescent sensor fields and for new material preparation. In addition to the large applicability, the homogeneous structure, high transparency and other specific properties of silica films are greatly dependent on the experimental conditions in a sol-gel process [18].…”
Section: Introductionmentioning
confidence: 99%
“…where I 0 is the maximum CL intensity for standard at t = 5 s and I is the maximum CL intensity for each sample at t = 5 s [25].…”
Section: Characterization Methodsmentioning
confidence: 99%
“…13,[20][21][22][23][24][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] Silica is an ideal robust coupling layer material to integrate nanocatalysts and magnetic components because of its excellent chemical affinity and thermal stability. 55 Moreover, among silica-based coupling layers, porous silica can not only be easily prepared but can provide large surface areas for loading a great number of nanocatalysts and/or act as a protective shell to prevent catalysts from leaching. [56][57][58][59][60] As such, it is frequently used in assisting in the fabrication of various MRNCs.…”
Section: Chao Zhoumentioning
confidence: 99%